AnalysÄ±s Of External Factors AffectÄ±ng Non PerformÄ±ng FÄ±nance (Npf) SharÄ±a Banks In IndonesÄ±a (PerÄ±od 2009 Q1-2018 Q4) - Muqorrobin, Yahya; Rahman, Asmak Ab; Maharani, Shinta (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
The high ratio of problematic financing or Non-Performing Finance (NPF) at Islamic banks is a phenomenon that needs attention because it is one indicator to assess the soundness of Islamic banks. The causative factors could be two-way, first, the internal factors in Islamic banking itself; the principle of prudence in channeling financing; and second, external factors. Economic data indicated a slowdown in global economic growth became a negative sentiment on the financial markets; one of the consequences was the weakening of the customer ability to meet their obligations would be increasing the ratio of problem financing (NPF). The purpose of this study is to analyze and identify the relationship between macro variables Gross Domestic Product (GDP), exchange rate, and inflation with NPF at Sharia Banks in Indonesia 2009: Q1 to 2018: Q4. This research is a quantitative study with the data analysis method used Auto-regressive Distributed Lag (ARDL) to analyze the relationship between independent variables on the dependent variable in the long term and short term. The result is that GDP has a negative and significant effect on NPF both in the long term and short term. In comparison, the exchange rate and inflation have a positive and significant effect on the NPF in the short run but have no significant effect in the long run.